Steganography Techniques for Digital Images - Yahya, Abid.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers newly developed and novel Steganography techniques and algorithms. The book outlines techniques to provide security to a variety of applications using Steganography, with the goal of both hindering an adversary from decoding a hidden message, and also preventing an adversary from suspecting the existence of covert communications. The book looks into applying these newly designed and improved algorithms to provide a new and efficient Steganographic system, called Characteristic Region-Based Image Steganography (CR-BIS). The algorithms combine both the robustness of the Speeded-Up Robust Features technique (SURF) and Discrete Wavelet Transform (DWT) to achieve characteristic region Steganography synchronization. The book also touches on how to avoid hiding data in the whole image by dynamically selecting characteristic regions for the process of embedding. Applies and discusses innovative techniques for hiding text in a digital image fileor even using it as a key to the encryption; Provides a variety of methods to achieve characteristic region Steganography synchronization; Shows how Steganography improves upon cryptography by using obscurity features.
Chapter1: Introduction to steganography -- Chapter2: Steganography techniques -- Chapter3: Characteristic region-based image steganography -- Chapter4: An enhanced robust and protected image steganographic system -- Chapter5: Conclusion towards hidden communication.
Keywords: Signal processing; Telecommunication; Computational intelligence; Image processing -- Digital techniques; Computer vision; Cryptography; Data encryption (Computer science).; Signal, Speech and Image Processing; Communications Engineering, Networks; Computational Intelligence; Computer Imaging, Vision, Pattern Recognition and Graphics; Cryptology